2019
DOI: 10.1530/jme-18-0148
|View full text |Cite
|
Sign up to set email alerts
|

HIF 1 inhibits STAR transcription and testosterone synthesis in murine Leydig cells

Abstract: Hypoxia-inducible factor-1 (HIF1) is a critical transcription factor involved in cell response to hypoxia. Under physiological conditions, its 'a' subunit is rapidly degraded in most tissues except testes. HIF1 is stably expressed in Leydig cells, which are the main source of testosterone for male, and might bind to the promoter region of steroidogenic acute regulatory protein (STAR), which is necessary for the testosterone synthesis, according to software analysis. This study aims to identify the binding site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…The expression of STAR was shown to be induced by HIF1 in mouse KK1 cells 18 . Conversely, the inhibitory action of HIF1 on STAR expression is documented in mouse Leydig cells 45 . Similar reports can be found that HIF1 could increase HSD3B expression in Leydig cells 46 , while others suggest that it may inhibit HSD3B and progesterone production in canine luteal cells 47 .…”
Section: Discussionmentioning
confidence: 98%
“…The expression of STAR was shown to be induced by HIF1 in mouse KK1 cells 18 . Conversely, the inhibitory action of HIF1 on STAR expression is documented in mouse Leydig cells 45 . Similar reports can be found that HIF1 could increase HSD3B expression in Leydig cells 46 , while others suggest that it may inhibit HSD3B and progesterone production in canine luteal cells 47 .…”
Section: Discussionmentioning
confidence: 98%
“…3 e, f, g and Table 2 ). For the selected genes expressed in testis, we observed that the expression levels of Pem (a well-defined androgen target gene) (Wang, et al, 2006 ) and Star (the first rate-limiting enzyme in testosterone synthesis) (Wang, et al, 2018 ) were reduced upon STAC3 ablation, whereas transcriptional levels of other rate-limiting enzymes (namely Hsd3b and Cyp11a1 ) were comparable in Ctrl sh and Stac3 sh-treated testes (Fig. 3 h).…”
Section: Resultsmentioning
confidence: 99%
“…The primers used were: mouse Stac3 (NM_177707.4), 5′-CCC ACT CTA CAG CGA CCA AC-3′ and 5′-GAC TCT GGC TCC TCC TCC AT-3′; rat stac3 (NM_001130558.1), 5′-ACT TCA GCT CTA CCA CCA CG-3′ and 5′-CTC CAT CTC GGT TGT CTC TGG-3′; human STAC3 (NM_145064.3), 5′-TTT CAG CCC TGA CAC CAA GG-3′ and 5′-ACT TTG CCG AGT CTC TGC TG-3′; human 18S (M10098.1, also applied to mouse and rat 18 s), 5′-AAT CAG GGT TCG ATT CCG GA-3′ and 5′-GTG GAC TCA TTC CAA TTA CAG-3′. Primers used for Pem, Star, Hsd3b and Cyp11a1 have been reported elsewhere (Wang, et al, 2006(Wang, et al, , 2018.…”
Section: Rt-qpcrmentioning
confidence: 99%
“…Previous in vitro studies and reports on HIF1α alterations in zebrafish larvae have suggested negative regulation of StAR, the mitochondrial cholesterol transporter (7,17,20). However, data on the effects of HPP alterations in adrenal cortex of mice is scant at best.…”
Section: Loss Of Phd2/hif1α In Adrenocortical Cells Impacts Gene Exprmentioning
confidence: 99%
“…Recent in vitro and zebrafish studies have revealed a continuous cross talk between HIF and steroidogenesis pathways, along with potential interference in the production of aldosterone and glucocorticoids (17)(18)(19)(20). There is also evidence suggesting a role for the hypoxia pathway in modulating glucocorticoid/glucocorticoid receptor (GR) signaling (21,22).…”
Section: Introductionmentioning
confidence: 99%